An Updated Insights into Vitamin D Receptor Gene Variation and Steroid Receptor Status in Breast Cancer Risk - Ashok Kumar Dogra (New Advances in Medicine and Medical Science Vol. 2, 2023)
This book chapter aims to analyze in a systematic way that the association of VDR allelic variants with breast cancer risk among patients from various populations. It have highlighted the new insights of the current understanding of molecular mechanisms of the VDR gene polymorphisms related to breast cancer risk and also examined the interaction between VDR polymorphisms and steroid hormone (estrogen, progesterone, and androgen) receptors and their modifying effects on breast cancer risk, cancer severity, progression rate, and disease outcome. This analysis has revealed that Fok1, Bsm1, Apa1 were to some extent associated with breast cancer risk, Taq1 shows no association, and Cdx2, poly(A), Tru91 gene polymorphisms may be susceptible for breast cancer development. Breast cancer is a compilation of distinct malignancies that manifests in the mammary glands. Carcinomas make up the majority of breast cancers while sarcomas such as phyllodes tumors and angiosarcomas are rarely seen. Vitamin D receptor (VDR) transcriptionally modifies its target genes involved in cell proliferation, differentiation, and apoptosis in a ligand-dependent manner, conferring a protective function against the development and spread of cancer. Numerous polymorphisms exist in the VDR gene’s coding and regulatory regions. (BsmI, Fok1, Taq1, Apa1, Cdx2, poly (A), etc.) that modulate its transcription, translation, and mRNA stability. Despite this, research in this area has not yet led to many conclusions. Vitamin D via VDR acts in a multitude of ways on cancer cell biology, including the cell cycle regulation, apoptosis, invasion, and metastasis, as well as angiogenesis, it has brought together a wide-ranging impact on tumor development under its domain. The study therefore advise that future research on genetic variations of the VDR gene be combined with the evaluation of the status of steroid hormone receptors in breast cancer due to the paucity of studies and inconsistent results.